Comparative Analysis of a Secondary Metabolite Profile from Leaves, Peel and Bulbs of Allium sativum L. by GC-MS - Hafizah, Gina Tasya Rizka; Hidayati, Agriana Rosmalina; Permatasari, Lina (Jurnal Biologi Tropis, 2024)
Garlic is a herbal plant that is widely used as a medicinal ingredient, because it contains secondary metabolite compounds such as alkaloids, flavonoids, tannins, phenols, terpenoids and saponins. The secondary metabolite content of plants is influenced by genetic, ontogenic, morphogenetic and environmental factors that can influence the biosynthesis and accumulation of secondary metabolites. Garlic is generally only used for the bulbs, while other parts such as the leaves and skin are still not widely used. This study aims to identify the secondary metabolite profile of ethanol extract of garlic leaves, bulbs and peels using the gas chromatography mass spectrometry (GC-MS) method. Identification of secondary metabolite compounds contained in each 70% ethanol extract was analyzed using the tube test, thin layer chromatography (TLC) and GC-MS methods. The results of analysis of secondary metabolite content using the tube test and TLC method showed that the ethanol extract of garlic leaves, skin and bulbs positively contained flavonoids, tannins, phenols and saponins. The results of secondary metabolite profile analysis using the GC-MS method from the ethanol extract of garlic skin and bulbs showed that 5 compounds were obtained with the main compound being 3,4-Dihydroxyphenylacetic acid and 23 compounds with the main compound being 1,2-Benzenedicaboxylic acid and palmitic acid, while the leek extract white only detected 1 compound. The conclusion is that the ethanol extract of garlic leaves, skin and bulbs has secondary metabolites in the form of flavonoids, tannins, phenols and saponins. There are differences in the profile of secondary metabolite compounds in the ethanol extract of garlic leaves, skin and bulbs in terms of the results of GC-MS analysis.